Tingkat Kecemasan Ibu Hamil Trimester III dalam Menghadapi Persalinan: Anxiety Levels of Third Trimester of Pregnant in Facing Childbirth - Siregar, Nilda Yulita; Kias, Cici Fitrayanti; Nurfatimah, Nurfatimah; Noya, Fransisca; Longgupa, Lisda Widianti; Entoh, Christina; Ramadhan, Kadar (Poltekkes Kemenkes Palu, 2021)
Introduction: Fear and anxiety during pregnancy and childbirth can cause problems such as preterm labor and low birth weight. Purpose: The purpose of this study was to determine the level of anxiety of third-trimester pregnant women in dealing with labor. Methods: This type of research is a descriptive study and analyzed with frequency distribution. The population was all pregnant women in the third trimester who were in the working area of ​​the Mapane Community Health Center with a total of 37 people. The sampling technique used total sampling. The results showed that only 8.1% of pregnant women experienced mild anxiety, while 91.9% did not experience anxiety. pregnant women who experience mild anxiety are 20% in the risk age group, 20% with diploma education, 11.5% in mothers who do not work, 60% in primigravidas, and 15.8% in mothers who do not get support from their husbands. Anxiety occurs mostly in primigravida because it is the first experience of pregnancy. It suggested for village midwives providing information about pregnancy and childbirth, especially for primigravida mothers, and involving their husbands in posyandu activities for pregnant women.